Sulfonamides and sulfonate esters: Synthetic routes, proposed mechanisms, and crystallographic characterizations - Stenfors, Brock Anton; Ngassa, Felix Nyuangem (European Journal of Chemistry, 2024)
The sulfonamide and sulfonate moieties are key structural features in many pharmaceuticals, agrochemicals, and materials and have proven useful as synthetic precursors. In this review, synthetic routes for sulfonamides and sulfonate esters were examined to gain insight into the mechanism behind the sulfonylation of amines and alcohols, which remains largely unknown and highly dependent on the reaction conditions used. Furthermore, the review delves into crystallographic characterizations of previously reported sulfonamide and sulfonate ester compounds, unraveling trends associated with crucial steric and electronic factors that influence their crystallization. This exploration not only enhances our understanding of the structural nuances of these compounds, but also paves the way for informed design strategies in synthetic and medicinal chemistry. In essence, this review endeavors to provide a holistic perspective on sulfonamides and sulfonate esters, bridging the realms of synthesis, mechanism elucidation, and structural characterization.